The essence gets to you - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Downtown in Kingston, Jamaica, in a bustling little area of new small businesses, stand two symbols of enterprises blowing new life into agricultural production. One is the LMH publishing company whose recent books on herbs, reviewed in this issue,...